Mata Kuliah Penulisan Karya Seni: Integrasi dan Kontribusinya pada Tugas Akhir Mahasiswa Program Studi Angklung dan Musik Bambu - Ega Fausta,; Whayan Christiana; Rizaldy Ramadhan (Paraguna, 2026)
This study aims to explore the integration of the Art Writing course and its contribution to supporting the final projects of students in the Angklung and Bamboo Music Study Program. The research employs a mixed-method approach, combining both quantitative and qualitative methods. Qualitative data were collected through literature review, observation, and semi-structured interviews to gain in-depth insights from students and lecturers. Quantitative data were gathered through a survey using a Likert scale to evaluate the correlation between the Art Writing course and students’ academic writing skills as well as their analysis of art works. The findings reveal that the integration of this course significantly contributes to enhancing students' abilities in composing final projects, particularly in terms of art work analysis and documentation. The Art Writing course functions not only as an academic support but also as a facilitator for the development of creative ideas and critical reflection on art works. In the context of traditional music art, the integration between writing and artistic practice strengthens the quality of students' final projects. Thus, this study has implications for curriculum development and more effective teaching approaches in the Angklung and Bamboo Music Study Program.